Prolonged myocardial protection with St. Thomas' Hospital solution and University of Wisconsin solution: The importance of preservation techniques - Karck, Matthias; Frantzen, V.; Schwalb, Herzl; Haverich, Axel; Uretzky, Gideon (European journal of cardio-thoracic surgery, 1992)
The effectiveness of University of Wisconsin solution (UWS) andoxygenated St. Thomas' Hospital solution (STS) for prolonged myocardialprotection was evaluated in isolated working rat hearts preserved for 12 hat 4 degrees C using three different preservation techniques: induction ofcardiac arrest and subsequent hypothermic storage with STS (group 1, n = 9)or UWS (group 4, n = 9), intermittent coronary flush (every 90 min) withSTS (group 2, n = 9) or UWS (group 5, n = 9), or continuous coronaryperfusion with STS (group 2, n = 7) or UWS (group 6, n = 7) before 60 minof reperfusion. In the UWS preserved hearts, recovery of aortic flow wasgreater when the simple storage technique was employed compared tointermittent or continuous coronary perfusion (groups 5 and 6). In the STSpreserved hearts, aortic flow recovery was superior when the intermittentperfusion technique was applied. The same pattern was observed with regardto recovery of left ventricular pressure. Lactate dehydrogenase releaseduring reperfusion was significantly less pronounced in group 4 (UWS,single flush, simple storage) as compared to group 1 (STS, single flush andsimple storage), whereas best preservation of myocardial high energyphosphates was observed when hearts were preserved with multiple dosecardioplegia using STS. Simple hypothermic storage with UWS affords thebest functional recovery after prolonged myocardial ischemia in all groups.Repetitive or continuous application of this solution is detrimental,possibly due to potassium overloading. In STS treated groups, multiple doseapplication of oxygenated STS enhances functional and metabolic recoverycompared to its single dose application.(ABSTRACT TRUNCATED AT 250WORDS)
Gesehen am 27.05.2022